Association of Mental Health-Related Proteins DAXX, DRD3, and DISC1 With the Progression and Prognosis of Chondrosarcoma - He, Lile; Shi, Xiangyu; Chen, Ruiqi; Wu, Zhengchun; Yang, Zhulin; Li, Zhihong (Frontiers in Molecular Biosciences, 2019)
Chondrosarcoma is the second most common malignant bone tumor. Current therapies remain ineffective, resulting in poor prognoses. Biomarkers for chondrosarcoma and predictors of its prognosis have not been established. Mental health–related proteins have been associated with the pathogenesis, progression, and prognosis of many cancers, but their association with chondrosarcoma has not been reported. In this study, the expression and clinicopathological significance of the mental health–related proteins DAXX, DRD3, and DISC1 in chondrosarcoma tissue samples were examined, over an 84-months follow-up period. In immunohistochemical analysis, the rates of positive DAXX, DRD3, and DISC1 expression were significantly higher in chondrosarcoma than in osteochondroma tissue (P < 0.01). The percentages of positive DAXX, DRD3, and DISC1 expression were significantly lower in tissues with good differentiation (P < 0.01), AJCC stage I/ II (P < 0.01), Enneking stage I (P < 0.01), and non-metastasis (P < 0.05), respectively. In Kaplan–Meier survival analysis, significantly shorter mean survival times were associated with moderate and poor differentiation (P = 0.000), AJCC stage III/IV (P = 0.000), Enneking stage II/III (P = 0.000), metastasis (P = 0.019), invasion (P = 0.013), and positive DAXX (P = 0.012), and/or DRD3 (P = 0.018) expression. In Cox regression analysis, moderate and poor differentiation (P = 0.006), AJCC stage III/IV (P = 0.013), Enneking stage II/III (P = 0.016), metastasis (P = 0.033), invasion (P = 0.011), and positive DAXX (P = 0.033), and/or DRD3 (P = 0.025) staining correlated negatively with the postoperative survival rate and positively with mortality. In competing-risks regression analysis, differentiation (P = 0.005), metastasis (P = 0.014), invasion (P = 0.028), AJCC stage (P = 0.003), Enneking stage (P = 0.036), and DAXX (P = 0.039), and DRD3(P = 0.019) expression were independent predictors of death from chondrosarcoma. The areas under receiver operating characteristic curves for DAXX, DRD3, and DISC1 expression were 0.673 (95% CI, 0.557–0.788; P = 0.010), 0.670 (95% CI, 0.556–0.784; P = 0.011), and 0.688 (95% CI, 0.573–0.802; P = 0.005), respectively. These results suggest that DAXX, DRD3, and DISC1 could serve as biomarkers of chondrosarcoma progression and predictors of its prognosis.